Ten steps to a results-based monitoring and evaluation system : a handbook for development practitioners - Kusek, Jody Zall, 1952-; Rist, Ray C. (Washington, DC : World Bank, 2004)
The focus of the handbook is on a comprehensive ten-step model that will help guide development practitioners through the process of designing and building a results-based M&E system. These steps begin with a "Readiness Assessment" and take the practitioner through the design, management, and, importantly, the sustainability of such systems. The handbook describes each step in detail, the tasks needed to complete each, and the tools available to help along the way.
Includes bibliographical references (p. 231-234) and index.
rpm 14/06/13
Loans
Keywords: Performance standards -- Developing countries -- Evaluation; Public administration -- Developing countries -- Evaluation; Total quality management in government -- Developing countries -- Evaluation; Government productivity -- Developing countries -- Evaluation